Comparison of complete and minimal mediastinal lymph node dissection for non‐small cell lung cancer: Results of a prospective randomized trial. Issue 4 (27th October 2013) - Zhang, Junhua; Mao, Teng; Gu, Zhitao; Guo, Xufeng; Chen, Wenhu; Fang, Wentao
Abstract: Background: To compare surgical results, pathological staging, and survival between complete and minimal mediastinal lymph node dissection for non‐small cell lung cancer (NSCLC). Methods: A randomized controlled trial was carried out in 202 patients who were assigned to undergo either skeletonized complete mediastinal lymph node dissection (CLD) or minimal mediastinal lymph node dissection (MLD). Clinical and pathological characteristics, surgical results, postoperative staging, and five‐year survival were recorded for statistical analysis. Results: Significantly more stations of lymph nodes were harvested through CLD, than MLD (8.9 vs. 6.2, P < 0.001). There was no difference in major complications (CLD 14.7% vs. MLD 14.0%, P = 0.884) or postoperative death (CLD 2.1% vs. MLD 1.9%, P = 0.904). No significant difference was detected in pathological staging between the two groups. The pN2 rates (27.1% vs. 24.2%), skip‐mediastinal metastasis (9.3% vs. 7.4%), and multi‐stational mediastinal involvement (15.0% vs. 16.8%) were similar between MLD and CLD. However, CLD had significantly better five‐year survival than MLD (55.7% vs. 37.7%, P = 0.005), especially in patients with a tumor size >3 cm, pleural invasion, pN1‐N2, stage II‐III, adenocarcinoma, and low‐differentiation carcinoma. Upon multivariate analysis, CLD, along with stage I and high‐differentiation, were independent prognostic factors for better overall survival. Conclusions: Complete and minimal mediastinal dissections have similar surgical risks and mediastinal staging effect in patients with NSCLC. Minimal dissection is enough for early stage high‐differentiation tumors. For patients with stage II‐III or low‐differentiation carcinoma, skeletonized complete mediastinal dissection may improve survival compared with minimal dissection.